PEKERJA PEREMPUAN DAN SEGMENTASI PASAR KERJA MENURUT WILAYAH KEBUDAYAAN DI PROVINSI JAWA TIMUR (ANALISA SAKERNAS 2012) - , PUPUT SETYANINGSIH; , Abdur Rofiâ, S.Si., M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The East Java Province developed as The Emerging Province of Indonesia. But The East Java Province face many challenges such as the difference of oppurtunity between women and men which then generates constraints. Population in The East Java Province have constructed a society based on indigenous cultural and social norms that are specific to each area. Stereotypical view of the differences between men and women was not realizing as a form of blockade of the influx of people in the labour market, particularly women. Even the labour market impact on the labour market segmentation. was to s This research ee how the labour market segmentation and female workers in The Jawa Timur Province culture by region was divided into four major culture areas that is Mataraman, Arekan, Pandalungan and Madura. Research segmentation of labor market by gender and specific characteristics of workers based main industry. The findes of this research, there are differences in labor market segmentation by sex in the divisions of culture at East Java Province. Full employment in the region of Madura culture especially for women are highly segmented in the agricultural sector, even women who segmented the highest agricultural sector in the area of culture Madura on non-agricultural sector. Full employment in the region Mataraman culture, Pandalungan and Arekanâs culture especially women in the field of business segmented in non-agricultural sector.